DEVELOPMENT OF INTERDISCIPLINER-BASED MATHEMATICS TEACHING MODULES IN THE INDEPENDENT CURRICULUM IN GRADE 1 SD - Urip umayah; Wahyu Setiyono (Jurnal Scientia, 2023)
This study aims to produce an interdisciplinary based mathematics teaching module on the independent curriculum in class I SD Negeri 01 Kalikudi that meets the valid, practical, and effective criteria. This type of research is development. The development research model used is the 4-D development model which defines, designs, develops, and disseminates. This research was conducted in the even semester of the 2022/2023 academic year. The research instruments included validation sheets, practicality sheets (teacher and student response questionnaires) and effectiveness sheets (pre-test and post-test questions). In the validation process, the module was validated by 1 material expert, 1 design expert and 1 linguist. In the practical process, the module was tried out by 1 teacher and 25 students. Based on the results of the research, the development of interdisciplinary based mathematics teaching modules in the independent curriculum in grade I SD produced modules that met very valid criteria with a vote percentage of 90.29%, met practical criteria with a percentage of 85.66% and met high effectiveness criteria with a percentage. of 0.71. So, it can be concluded that the mathematics teaching module based on the interdisciplinary based mathematics teaching module on the independent curriculum in grade I SD is valid, practical and effective as a resource in learning Mathematics in grade I Elementary School.